ANALISIS KEBUTUHAN VIDEO DALAM PEMBELAJARAN ERHADAP PEMAHAMAN PESERTA DIDIK DI MIN 1 BARITO SELATAN - ARDIANSYAH ARDIANSYAH (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2023)
This research is quantitative research. This research focuses on analyzing students' needs for learning videos in Mathematics subjects at MIN 1 South Barito. The aim of this research is to determine students' needs for the use of learning videos at MIN 1 South Barito. The samples used in this research were 10 students in class III (three), 10 (ten) class V (five) students and 10 students in class IV (six). The techniques for collecting information used were observation, interviews and questionnaires. The instrument used in this research was a questionnaire. The research results show that around 96.67% of students have cellphones as a means of support (29 people) and on average use cellphones for more than 10 hours per day. Regarding internet network availability, Wifi is available at school with a percentage of student answers of 100%. Around 90% of teachers use videos for learning at MIN 1 South Barito and according to students, using videos in learning is very enjoyable with a percentage of 93.34%. The use of videos in learning can help students understand 90%. The learning videos used by teachers are downloaded from the internet with 93.33% student answers. According to students, it is easier for them to understand if the learning video is made by the teacher concerned, with an answer percentage of 96.67% and 90% of students stating that the learning video is very helpful in completing homework. It can be concluded that students respond positively to the use of video as a medium in learning, so it will be more effective if subject teachers have learning media in the form of videos that they make themselves to better suit the students' needs. ABSTRAKPenelitian ini merupakan penelitian kuantitatif. Penelitian ini berfokus pada analisis kebutuhan peserta didik terhadap video pembelajaran pada mata pelajaran Matematika di MIN 1 Barito Selatan. Tujuan dari penelitian ini adalah untuk mengetahui kebutuhan peserta didik terhadap pemanfaatan video pembelajaran di MIN 1 Barito Selatan. Sampel yang digunakan pada penelitian ini adalah peserta didik kelas III (tiga) berjumlah 10 orang, kelas V (lima) berjumlah 10 (sepuluh) orang dan kelas IV (enam) berjumlah 10 orang. Teknik dalam mengumpulkan informasi yang digunakan  adalah observasi, wawancara, dan kuesioner. Instrumen yang digunakan dalam penelitian ini adalah kuesioner. Hasil penelitian menunjukkan bahwa peserta didik yang mempunyai HP sebagai sarana pendukung sekitar 96,67% (29 orang) dan rata-rata penggunaan HP lebih dari 10 jam per hari. Untuk ketersediaan jaringan internet, di sekolah sudah tersedia Wifi dengan persentase jawaban peserta didik sebesar 100%. Guru yang memanfaatkan video untuk pembelajaran di MIN 1 Barito Selatan sekitar 90% dan menurut peserta didik, penggunaan video dalam pembelajaran sangat menyenangkan dengan persentase 93,34%. Penggunaan video dalam pembelajaran dapat membantu pemahaman peserta didik 90%. Video pembelajaran yang digunakan oleh guru merupakan hasil download dari internet dengan jawaban peserta didik 93,33%. Menurut peserta didik, mereka lebih mudah memahami apabila video pembelajaran tersebut dibuat oleh guru yang bersangkutan, dengan persentase jawaban 96,67% dan 90% peserta didik menyatakan bahwa video pembelajaran sangat membantu dalam menyelesaikan pekerjaan rumah. Dapat disimpulkan bahwa peserta didik merespon positif penggunakan video sebagai media dalam pembelajaran, sehingga akan lebih efektif apabila guru mata pelajaran mempunyai media pembelajaran berupa video yang dibuat sendiri agar lebih sesuai dengan kebutuhan peserta didik.